Personality and Walking Speed Across Adulthood: Prospective Evidence From Five Samples. Issue 7 (September 2018) - Stephan, Yannick; Sutin, Angelina R.; Bovier-Lapierre, Gabriel; Terracciano, Antonio
Walking speed is one marker of health in adulthood. Although personality may contribute to gait speed, there is limited longitudinal data on this association. Thus, the present study examined whether personality traits are prospectively associated with walking speed among middle aged and older adults. Participants were adults aged from 25 to 100 years old ( N > 15, 000) drawn from the Wisconsin Longitudinal Study Graduate and Sibling samples, the Midlife in the United States Survey, the Health and Retirement Study, and the National Health and Aging Trends Survey. Across most samples and in a meta-analysis, lower neuroticism and higher extraversion, conscientiousness, and openness at baseline were prospectively related to faster gait speed. In the HRS, lower neuroticism and higher extraversion, conscientiousness, and openness were related to slower gait speed decline. This study provides robust evidence that walking speed in adulthood reflects, in part, the individual's personality.